Generality in the form of distribution of light and ionization along the trace of meteors of different ranges intensities - Нарзиев, М.; Шоекубов, Ш.Ш. (Radiotekhnika, 2020)
The purpose of this work is to study the distribution of brightness and ionization along the wake of meteors recorded by optical and radar equipment in a wide range of speeds, brightnesses, and to study the dependence of the shape of the light and ionization curves of meteors on their speed and mass of meteoroids. A general tendency is revealed in the histogram of the distribution of meteors by the parameter P (the location of the height of the maximum of the glow or ionization relative to the height of the beginning and end of the trail) in a wide range of magnitudes. It is established that the distribution forms of meteoroids with respect to the parameter P in both optical and radar data are asymmetric. The increase in the number of meteors in the first half of all histograms occurs approximately exponentially, and the decrease in the number of meteors after the maximum occurs relatively slowly. According to optical and radar observations, the dependence of the parameter P on such parameters of the atmospheric trajectory as: velocities, zenith distances of the radiant and the mass of meteors has been studied.